Reliability of RT-qPCR Pooling Method for COVID-19 Detection in Various Cycle Threshold Values - Radjawali, Muhammad Fauzan Alif; Jihadah, Muti'ah; Chaidir, Lidya (Faculty of Medicine Universitas Padjadjaran, 2023)
Background: Reverse Transcriptase Quantitative Real-time Polymerase Chain Reaction (RT-qPCR) is a standard method to detect SARS-CoV-2, the cause of COVID-19 disease, albeit expensive for some laboratory settings. The pooling test is widely used for large-scale screening to speed up the turn-around time and reduce the cost of the RT-qPCR. However, the pooling test involves mixing a certain number of specimens which theoretically increases the possibility of false-negative results. This study aimed to evaluate the accuracy of the pooling test compared with the non-pooling test in different Ct values as a surrogate for viral load.Methods: RT-qPCR was performed in three groups of samples: non-pooling (individual samples), pooling of 5 samples and 11 samples, with various ranges of Ct value in the respective group: x<25 (n=4); 25<x<30 (n=5), x<30 (n=16), and negative sample (n=5). Agreement and kappa values were calculated. Four of twenty-five individual samples resulted in false-negative after pooling.Results: By taking all samples without applying the cut-off value to the calculation, the agreement in pooling of 5 samples was 0.86 (Kappa 0.31) and of 11 samples was 0.64 (Kappa 0.96). When the cut-off value of Ct<37 was applied, percent agreement and kappa were 1.00, respectively, for both pooling methods.Conclusions: Pooling up to 11 samples shows high concordance with RT-qPCR with individual samples with Ct<37. Interpreting pooling results in a very low viral load (Ct≥37) must be considered due to the increased possibility of inconclusive results.